Optimization of the air separation process in single stage cryogenic units - Ionita, Claudia; Vasilescu, Elena-Eugenia; Stanciu, Camelia; Pop, Horatiu; Popa, Lucretia (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The industrial use of cryogenic air separation units started more than 130 years ago. Cryogenic air separation units produce oxygen, pure nitrogen and argon in liquid and/or gaseous state. Different configurations of these cryogenic plants lead to different quantities of gas and liquid products. In addition, product purity is also affected by the proposed scheme. As a result, the paper analyzes different variants of installations for the separation of binary gas mixtures based on the Linde process. By comparing energy indices and constructive considerations, the separation plant with external air pre-cooling and the use of a single-stage separation column is chosen. Finally, a study is carried out on the processes in the separation column and a calculation of the minimum mechanical work of separation. The real air consumption curve will also be built, with the help of which we shall determine what quantities of O2 and N2 are obtained by air separation at a specific consumption.